An Installed Tape Automated Bonding Unit. (1980) - Kurzweil, Karel
Abstract : The Tape Automated Bonding (TAB) was developed and industrialized to achieve a higher packaging density in computer applications. After elaboration and testing of the prototype units, significant work was done to transfer all the activity into production. After a brief review of the principle of TAB technology the main characteristics of the manufacturing site are presented and the most significant equipments developed for production needs are briefly described. It becomes apparent that TAB and micropackaging technology are not limited to computers but can be considered in many other microelectronic applications.